Analyzing Action/Plan Consistency: The Role of the Staff Report. Issue 1 (2nd January 2021) - Ohm, Brian W.
Abstract: Problem, research strategy, and findings: An increasing number of laws throughout the United States require that local officials articulate the reasons for their decisions related to land use matters. These include the legal basis for the decision and the factual basis of the particular matter. Although there is not much research on the role of planning staff reports in the planning process, staff reports become part of the record and can provide legitimacy for a decision. In this study I summarize the legal requirements found in many states that certain local decisions must be consistent with a locally adopted comprehensive plan. I analyze how planning staff reports evaluate consistency. Many staff reports fail to provide decision makers with an analysis of how a proposed action relates to the policies in the plan. Takeaway for practice: A comprehensive plan is more than a future land use map. Planning staff reports need to provide the framework for an analysis of how a proposed action relates to the community's plan as a whole and give meaning to the concept of consistency. Staff reports should inform decision makers about the content of the plan, thereby reminding decision makers of the existence of the plan, and evaluate how the proposed action relates to the policies in the plan through a narrative that reinforces the value of planning.